The Role of Social Media in Forming Social Solidarity Among Millennials in The Post-Truth Era - Ahmad Mubarok; Rosmaria Rosmaria (Archipel: Journal of Indonesian Interdisciplinary Studies, 2026)
The post-truth era has fundamentally altered the information landscape, creating unique challenges and opportunities for the formation of social solidarity among millennial generations who rely heavily on social media as their primary mode of communication and community building. This study examined the role of social media in shaping social solidarity among millennials under conditions characterized by widespread disinformation, echo chambers, and political polarization. Methods: A systematic literature review was conducted, analyzing 20 peer-reviewed studies published between 2021 and 2024 that addressed social media use, millennial behavior, solidarity formation, and post-truth dynamics. Studies were retrieved from multiple academic databases using structured search protocols. Results: Social media platforms, particularly Instagram, WhatsApp, and YouTube, served as primary channels for millennial social solidarity expression, including hashtag activism, peer endorsement, and digital community building. Post-truth phenomena, including fake news, echo chambers, and political polarization, simultaneously threatened and paradoxically reinforced in-group solidarity mechanisms. Influencers and digital opinion leaders played a mediating role in shaping collective values and community norms. Counter-solidarity effects were most pronounced in politically charged contexts. Conclusions: Social media operates as a dual-edged mechanism in millennial social solidarity formation during the post-truth era. Strategic digital literacy interventions, platform governance reforms, and community-based trust-building are essential to harness the solidarity-promoting potential of social media while mitigating divisive forces rooted in disinformation and polarization.